Selective IgM Deficiency: Clinical and Laboratory Features of 17 Patients and a Review of the Literature - Chovancova, Zita; Kralickova, Pavlina; Pejchalova, Alena; Bloomfield, Marketa; Nechvatalova, Jana; Vlkova, Marcela; Litzman, Jiri (Journal of clinical immunology, 2017)
PURPOSE: Primary selective IgM deficiency (sIgMD) is a primary immunodeficiency with unclear pathogenesis and a low number of published cases. METHODS: We reviewed clinical and laboratory manifestations of 17 sIgMD patients. Serum IgM, IgG, and its subclasses, IgA, IgE, antibodies against tetanus toxoid, pneumococcal polysaccharides and Haemophilus influenzae type b, isohemagglutinins, and T and B lymphocyte subsets, expressions of IgM on B cells and B lymphocyte production of IgM were compared with previously reported case reports and a small series of patients, which included 81 subjects in total. RESULTS: We found that some patients in our cohort (OC) and published cases (PC) had increased IgE levels (OC 7/15; PC 21/37), decreased IgG4 levels (OC 5/14), very low titers of isohemagglutinins (OC 8/8; PC 18/21), increased transitional B cell counts (OC 8/9), decreased marginal zone B cell counts (OC 8/9), and increased 21low B cell counts (OC 7/9). Compared with the PC (20/20), only two of five OC patients showed very low or undetectable production of IgM after stimulation. A majority of the patients had normal antibody production to protein and polysaccharide antigens, basic lymphocyte subset counts, and expression of surface IgM molecules on B cells. CONCLUSIONS: Low IgM levels are associated with various immunopathological disorders; however, pathogenic mechanisms leading to decreased IgM serum level in selective IgM deficiency remain unclear. Moreover, it is difficult to elucidate how strong these associations are and if these immunopathological conditions are primary or secondary.
Keywords: dospělí; autoimmunity; Female; Autoimmunity; imunoglobulin G; Adult; mladý dospělý; ženské pohlaví; syndromy imunologické nedostatečnosti; infections; imunoglobulin M; lidé; infekce; Immunoglobulin E; allergy; Infections; Immunoglobulin G; kohortové studie; Cohort Studies; Selective IgM deficiency; Immunologic Deficiency Syndromes; Male; Aged; Immunoglobulin M; Young Adult; B-Lymphocytes; imunoglobulin E; B-lymfocyty; autoimunita; primary immunodeficiency; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans